A Microbial Mutualist Within Host Individuals Increases Parasite Transmission Between Host Individuals: Evidence From a Field Mesocosm Experiment - O’Keeffe, Kayleigh R.; Wheeler, Brandon T.; Mitchell, Charles E. (Frontiers in Microbiology, 2022)
The interactions among host-associated microbes and parasites can have clear consequences for disease susceptibility and progression within host individuals. Yet, empirical evidence for how these interactions impact parasite transmission between host individuals remains scarce. We address this scarcity by using a field mesocosm experiment to investigate the interaction between a systemic fungal endophyte, Epichloë coenophiala, and a fungal parasite, Rhizoctonia solani, in leaves of a grass host, tall fescue. Specifically, we investigated how this interaction impacted parasite transmission under field conditions in replicated experimental host populations. Epichloë-inoculated populations tended to have greater disease prevalence over time, though this difference had weak statistical support. More clearly, Epichloë-inoculated populations experienced higher peak parasite prevalences than Epichloë-free populations. Epichloë conferred a benefit in growth; Epichloë-inoculated populations had greater aboveground biomass than Epichloë-free populations. Using biomass as a proxy, host density was correlated with peak parasite prevalence, but Epichloë still increased peak parasite prevalence after controlling for the effect of biomass. Together, these results suggest that within-host microbial interactions can impact disease at the population level. Further, while Epichloë is clearly a mutualist of tall fescue, it may not be a defensive mutualist in relation to R. solani.